Applied business statistics making better business decisions - Black, Ken., author (2013)
Black's latest outstanding pedagogy of Business Statisticsincludes the use of extra problems called "Demonstration Problems"to provide additional insight and explanation to working problems,and presents concepts, topics, formulas, and application in amanner that is palatable to a vast audience and minimizes the useof "scary" formulas.